Effects of n-6 PUFAs compared with SFAs on liver fat, lipoproteins, and inflammation in abdominal obesity: a randomized controlled trial - Bjermo, Helena; Iggman, David; Kullberg, Joel; Dahlman, Ingrid; Johansson, Lars; Persson, Lena; Berglund, Johan; Pulkki, Kari; Basu, Samar; Uusitupa, Matti; Rudling, Mats; Arner, Peter; et al. (The American journal of clinical nutrition, 2012)
Replacing SFAs with vegetable PUFAs has cardiometabolic benefits, but the effects on liver fat are unknown. Increased dietary n-6 PUFAs have, however, also been proposed to promote inflammation-a yet unproven theory. We investigated the effects of PUFAs on liver fat, systemic inflammation, and metabolic disorders. We randomly assigned 67 abdominally obese subjects (15% had type 2 diabetes) to a 10-wk isocaloric diet high in vegetable n-6 PUFA (PUFA diet) or SFA mainly from butter (SFA diet), without altering the macronutrient intake. Liver fat was assessed by MRI and magnetic resonance proton (1H) spectroscopy (MRS). Proprotein convertase subtilisin/kexin type-9 (PCSK9, a hepatic LDL-receptor regulator), inflammation, and adipose tissue expression of inflammatory and lipogenic genes were determined. A total of 61 subjects completed the study. Body weight modestly increased but was not different between groups. Liver fat was lower during the PUFA diet than during the SFA diet [between-group difference in relative change from baseline; 16% (MRI; P < 0.001), 34% (MRS; P = 0.02)]. PCSK9 (P = 0.001), TNF receptor-2 (P < 0.01), and IL-1 receptor antagonist (P = 0.02) concentrations were lower during the PUFA diet, whereas insulin (P = 0.06) tended to be higher during the SFA diet. In compliant subjects (defined as change in serum linoleic acid), insulin, total/HDL-cholesterol ratio, LDL cholesterol, and triglycerides were lower during the PUFA diet than during the SFA diet (P < 0.05). Adipose tissue gene expression was unchanged. Compared with SFA intake, n-6 PUFAs reduce liver fat and modestly improve metabolic status, without weight loss. A high n-6 PUFA intake does not cause any signs of inflammation or oxidative stress. Downregulation of PCSK9 could be a novel mechanism behind the cholesterol-lowering effects of PUFAs. This trial was registered at clinicaltrials.gov as NCT01038102.